(untitled) (Fiep Bulletin - online, 2014)
We conclude that with the questions related to the following structures: heart, spleen, thyroid, kidney, carpal bones, fibula, radio, clavicle, femur, rotator cuff, biceps, supinator, quadriceps, pectineus, tarsal bones, cremaster muscle, tibia and deltoid, where 273 students were investigated of the morning and evening: 76 students of Physiotherapy; 136 students of Nursing and 61 students of Physical Education concluded that for these classes has the following percentage of success for students of Physical Education : heart (39%), spleen (13%), thyroid (41%), kidney (39%), carpal bones (34%), fibula (31%), radio (28%); clavicle (36%); femur (31%); rotator cuff (25%); biceps brachial (41%); supinator (28%); quadriceps (34%); pectineal (31%); tarsal bones (41%); cremaster muscle (00%), tibia (36%), deltoid (23%), where all the structures were below 50% of hits. Nursing to the class have the following arrangements: heart (100%), spleen (21%), thyroid (93%), kidney (67%), the carpal bones (54%), the fibula (44%); radio (53%); clavicle (86%); femur (86%); rotator cuff (22%); biceps brachial (48%); supinator (18%); quadriceps (23%); pectineal (20%); tarsal bones (37%); cremaster muscle (00%), tibia (24%), deltoid (15%), where all the structures that were below 50 % of hits were spleen, fibula, rotator cuff, biceps, supinator, quadriceps, pectineus, tarsal bones, cremaster muscle, tibia and deltoid. Physiotherapy to the class have the following arrangements: heart (100%), spleen (21%), thyroid (91%), kidney (65%), the carpal bones (54%), the fibula (54%); radio (51%); clavicle (86%); femur (86%); rotator cuff (21%); biceps brachial (96%); supinator (17%); quadriceps (26%); pectineal (13%); tarsal bones (71%); cremaster muscle (07%), tibia (68%), deltoid (34%), where the following structures were below 50 % of hits: spleen, rotator cuff, supinator, quadriceps, pectineus, cremaster muscle and deltoid. It was concluded that in relation to classes and anatomical structures of classes of Physiotherapy, Nursing and Physical Education is very low in relation to the following structures: spleen, rotator cuff, supinator, cremaster muscle, quadriceps, pectineus, fibula, biceps, bones tarsus, tibia and deltoid.